PENGEMBANGAN MEDIA MEMAHAMI KALIMAT (MAMAT) BERBASIS ARTICULATE STORYLINE UNTUK SISWA KELAS III PADA MUATAN PELAJARAN BAHASA INDONESIA - Lilis Maulidiah Astuti; Treny Hera; Sonia Anisah Utami (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop MAMAT learning media based on articulate storyline in learning Indonesian Language Theme 5 Subtheme 1 Lesson 1 Effective Sentence Material that is valid and practical. The type of research used in this study is research and development (R&D) referring to the ADDIE model with stages, namely Analysis, Design, Development, Implementation, Evaluation. Based on expert tests from validators covering three aspects, namely media, language, and materials, the results of this study obtained an average percentage of 88.2% with the category